Optimasi Rute Pengiriman dengan Heterogeneous Fleet Vehicle Routing Problem with Time Windows - Edwin Hendrawan; I Gede Agus Widyadana (Universitas Serang Raya, 2018)
PT. X is a distributor of spare parts with 128 customers for Surabaya City and Sidoarjo City. Number of delivery vehicles owned by PT. X is 15. Determination of delivery route owned by PT. X is completed manually based on driver experience. This research is to make a model of determining the route with minimum cost by considering the travel time and the capacity of the vehicle. Model formation is accomplished in accordance with the PT X policy that each colleague can only be served by one vehicle and the maximum shipping time of 7 hours. The model formed is Heterogeneous Fleet Vehicle Routing Problem with Time Windows (HFVRPWTW). The settlement method used is Evolutionary Algorithm (EA) by reviewing 3 cases. The number of vehicles decreased by the model is with an average difference of 1.67 vehicles. The shipping cost generated by the model is lower than the company for case 1 of 3,155 IDR and case 2 of 25,005 IDR. This condition indicates the model will use less number of vehicles with low shipping costs and large container utilities in 2 cases.